Biogenic Synthesis of Gold Nanoparticles on a Green Support as a Reusable Catalyst for the Hydrogenation of Nitroarene and Quinoline. Issue 14 (15th June 2021) - Adeyeye Nafiu, Sodiq; Shaheen Shah, Syed; Aziz, Abdul; Shaikh, M. Nasiruzzaman
Abstract: Direct attachment of gold nanoparticles to a green support without the use of an external reducing agent and using it for removing toxic pollutants from wastewater, i. e., reduction of nitroarene to amine, are described. A novel approach involving the reduction of gold by the jute plant ( Corchorus genus ) stem‐based (JPS) support itself to form nanoparticles (AuNPs) to be used as a catalytic system ('dip‐catalyst') and its catalytic activity for the hydrogenation of series of nitroarenes in aqueous media are presented. AuNPs/JPS catalyst was characterized using SEM, UV‐Vis, FTIR, TEM, XPS, and ICP‐OES. Confined area elemental mapping exhibits uniform and homogeneous distribution of AuNPs on the support surface. TEM shows multi‐faceted AuNPs in the range of 20–30 nm. The reactivity of AuNPs/JPS for the transfer hydrogenation of nitroarene as well as hydrogenation of quinoline under molecular H2 pressure was evaluated. Sodium borohydride, when used as the hydrogen source, demonstrates a high catalytic efficiency in the transfer hydrogenation reduction of 4‐nitrophenol (4‐NP). Quinoline is quantitatively and chemoselectively hydrogenated to 1, 2, 3, 4‐tetrahydroquinoline (py‐THQ) using molecular hydrogen. Reusability studies show that AuNPs are stable on the support surface and their selectivity is not affected. Abstract : A dip catalyst consisting of gold nanoparticles (20 –30 nm) immobilized on the surface of thin slices of jute‐stem was fabricated without any external reducing agent. The versatility of the catalyst for both hydrogen transfer reaction of nitroaromatics and quinoline hydrogenation under molecular hydrogen was demonstrated.